Initial Coupling and Reaction Progression of Directly Deposited Biradical Graphene Nanoribbon Monomers on Iodine-Passivated Versus Pristine Ag(111) - Galeotti, Gianluca; Fritton, Massimo; Lischka, Matthias; Obermann, Sebastian; Ma, Ji; Heckl, Wolfgang M.; Feng, Xinliang; Lackinger, Markus (Chemistry, 2022)
The development of widely applicable methods for the synthesis of C-C-bonded nanos-tructures on inert and insulating surfaces is a challenging yet rewarding milestone in the field of on-surface synthesis. This would enable studies of nearly unperturbed covalent nanostructures with unique electronic properties as graphene nanoribbons (GNR) and π-conjugated 2D polymers. The prevalent Ullmann-type couplings are almost exclusively carried out on metal surfaces to lower the temperature required for initial dehalogenation well below the desorption threshold. To overcome the necessity for the activation of monomers on the target surface, we employ a recently developed Radical Deposition Source (RaDeS) for the direct deposition of radicals onto inert surfaces for subsequent coupling by addition reactions. The radicals are generated en route by indirect deposition of halogenated precursors through a heated reactive tube, where the dehalogenation reaction proceeds. Here, we use the ditopic 6,11-diiodo-1,2,3,4-tetraphenyltriphenylene (DITTP) precursor that afforded chevron-like GNR on Au(111) via the usual two-staged reaction comprised of monomer-coupling into covalent polymers and subsequent formation of an extended GNR by intramolecular cyclodehy-drogenation (CDH). As a model system for inert surfaces, we use Ag(111) passivated with a closed monolayer of chemisorbed iodine that behaves in an inert manner with respect to dehalogenation reactions and facilitates the progressive coupling of radicals into extended covalent structures. We deposit the DITTP-derived biradicals onto both iodine-passivated and pristine Ag(111) surfaces. While on the passivated surface, we directly observe the formation of covalent polymers, on pristine Ag(111) organometallic intermediates emerge instead. This has decisive consequences for the further progression of the reaction: heating the organometallic chain directly on Ag(111) results in complete desorption, whereas the covalent polymer on iodine-passivated Ag(111) can be transformed into the GNR. Yet, the respective CDH proceeds directly on Ag(111) after thermal desorption of the iodine passivation. Accordingly, future work is aimed at the further development of approaches for the complete synthesis of GNR on inert surfaces.
CRIS-Team Scopus Importer:2023-03-20
Keywords: graphene nanoribbon; inert surfaces; radical addition; radical deposition; scanning tunneling microscopy